Analisis Program Magang Jepang Dalam Penciptaan Lapangan Kerja Baru (Studi Pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Jawa Timur) - Azizah, Nur Laily; Anshari, Ach. Zainal (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2024)
Qualitative research which aims to answer questions about how the Japanese internship program is implemented at the East Java Province Manpower and Transmigration Service and how effective the Japanese internship program is in creating new jobs.The research method used is a descriptive qualitative approach with a type of research study on objects. Data collection was carried out by interviews with informants in this research, namely the head of the management development section of the East Java Provincial Manpower and Transmigration Service, the selection committee for the Japanese internship program, Japanese post-internships.The results of this research conclude that the implementation of the Japanese internship program can be said to be effective because it is in accordance with existing regulations but there are few obstacles when conducting outreach to each district or city with regional autonomy. Regarding the effectiveness of the Japanese internship program in creating new jobs when they return to Indonesia, based on research results, Japanese internship activities can have a positive impact, namely being able to create independent entrepreneurs in both business and service sectors and having employees, and providing more effective work opportunities by utilizing certificates. to apply for jobs in Indonesia, both private and public.